Variáveis preditivas das alterações no posicionamento da coluna cervical com a biomecânica da deglutição em indivíduos com DPOC - Bilheri, Diego Fernando Dorneles (2022)
Chronic Obstructive Pulmonary Disease (COPD), multifactorial disease, is characterized by airflow limitation and is usually associated with chronic diseases that increase the morbidity and mortality of the subject flows. Studies show changes in swallowing biomechanics, such as impaired breathing/swallowing coordination, pharyngeal stasis, delayed swallowing triggering and decreased laryngeal elevation during swallowing, cricopharyngeal muscle dysfunction and impaired laryngopharyngeal sensitivity. However, there is a lack of studies investigating the relationship between changes in swallowing biomechanics related to cervical spine curvature. The aim of the study was to investigate the relationship between cervical spine curvature and swallowing biomechanics in individuals with COPD and to identify predictors for changes in swallowing efficiency in these subjects To this end, a quantitative, descriptive and analytical, cross-sectional and controlled study was carried out in individuals with a diagnosis of COPD, under follow-up at the pulmonology outpatient clinic and in the Physiotherapy sector of the University Hospital of Santa Maria (HUSM) in the period of August 2017 to March 2020. The modified Cobb method (C2-C4) was used to assess the curvature of the cervical spine and the ASPEKT-C method to assess the biomechanics of swallowing. Based on these assessments, we observed that the curvature of the cervical spine of individuals with COPD, using the modified Cobb angle, was 29.62º (±11.36) degrees. The set of variables sex, age, height, weight, BMI and disease severity were predictors of cervical spine angulation (adjusted R2 = 0.32). In addition, we observed the presence of total pharyngeal residues and the curvature of the cervical spine proved to be a predictor for pharyngeal residues (adjusted R2 = 0.20). In view of the above, we conclude that individuals with COPD present cervical spine curvature greater than that observed in the literature in normal individuals, according to the modified Cobb angle and the set of variables sex, age, height, weight, BMI and GOLD are predictors for changes in the curvature of the cervical spine. In addition, we identified that individuals with COPD have pharyngeal residues and deficits in pharyngeal constriction when evaluated by the ASPEKT-C method, and these changes in efficiency are predictors of changes in swallowing safety. The curvature of the cervical spine of these subjects proved to be a predictor for the presence of pharyngeal residues.